Tumefactive multiple sclerosis - Michael Gregorio Ortega-Sierra; Raul David Delgado-Marrugo; Cristian Camilo Campo-Bedoya; Geraldine Marín-Pérez; Rhonald Gómez-Caballero; Bryan D. Hernández-Nieto; Gabriel Fernando Gutiérrez-Castillo; John Fredys Bello-Cordero; Mónica Alejandra Torres-Báez; Rafael Ricardo Ramirez-Morales; Ivan David Lozada-Martinez; Luis Rafael Moscote-Salazar (Romanian Neurosurgery, 2021)
Tumefactive multiple sclerosis is a rare variant of multiple sclerosis, characterized by the presence of brain lesions that may be solitary or multiple. Considering that these lesions have a pseudotumoral appearance, it is a challenge to differentiate them from central nervous system neoplasms through neuroimaging. Many cases are associated with the administration of monoclonal antibodies, and due to an increase in the incidence of cancer globally, it is expected that secondary to chemotherapeutic treatments, more and more cases may appear. Taking into account the above, the objective of this review is to review aspects of usefulness in clinical practice, on the diagnosis and approach of this pathological condition